Capturing Results a Better Way : Eight Lessons in Productive Data Collection - Hossain, Mustahid (World Bank, Washington, DC, 2012)
Although many development partners have been discussing impact and evaluation for the last 30 years of international development, there still seems to be disagreement on indicators, impact, and how to collect the data, and discussions are ongoing. Evaluations and impact assessments are crucial for International Finance Corporation (IFC) advisory services projects. They help identify issues in implementing strategies that ultimately stand in the way of realizing the project's goals and provide vital lessons for the success of future endeavors. Based on experiences at the IFC South Asia Enterprise Development Facility (SEDF), the authors want to share some lessons on how to collect monitoring and evaluation (M&E) data in the most effective way and what data to look for.